Torsion of an Epididymal Cyst: A Rare Finding on Scrotal Exploration for Acute Scrotum - A. M. Omar Mohamed Ozaal; B. Pragalathan; S. Lavanya; S. T. Sarma (Case Reports in Urology)
Torsion of epididymal cyst (EC) is an exceedingly rare cause of acute scrotum in both children and adults. We add our case as the ninth case to literature which was an 8-year-old child presented with features of acute scrotum with history of EC on conservative management. Doppler sonography showed perfused normal bilateral testes and a 4.1×1.7  cm septate cystic lesion of right epididymis. On scrotal exploration, we found a haemorrhagic cystic lesion attached to the upper pole of right testis and twisted for 540 degrees with normal testis and appendage. Cyst was excised, and histopathology revealed a haemorrhagic EC. Our case was peculiar due to, presenting as acute scrotum in a child of 1-10 years age group who was conservatively managed for right-sided EC and presence of 540 degrees torsion.